(untitled) (Research, Society and Development, 2022)
Self-medication is considered a health problem in Brazil and worldwide. Several factors allow such practice, for instance difficulty in accessing doctors and easy access to medicines, marketing, internet and knowledge about the illness and the medicines. Although self-medication has advantages, the problems arising from its practice are more worrying. This study aimed to conduct an integrative review on the panorama of self-medication among nursing and medical students in Brazil. The databases Medline, Lilacs and BDENF in the Biblioteca Virtual as Saúde were scrutinized using “automedicação”, “estudantes de enfermagem” and “estudantes de medicina” key words, between September 2020 and January 2021. Fifteen articles were obtained from wich 53.3% including medical students, 26.6% nursing students and 20% students from both courses. Most publications are from 2019 (26.6%), from the state of Sâo Paulo (40%), and 60% are Lilacs database indexed. The use of analgesics as self-medication was prevalent in 86.6% of the included studies, and that female students are more related to this practice. Self-medication is not a practice that should be eliminated, but used with caution, following correct guidelines, however, it is necessary to change paradigms in academic training to create more qualified professionals aiming at patient safety.